(untitled) (Revista Innova Educación, 2025)
This study stems from the problem of updating the curriculum in teacher education at an educational institution in northeastern Mexico (the Autonomous University of Nuevo León, UANL), specifically the psychopedagogical curricular track in terms of content, strategies, updating, and professional development to strengthen the professional profile across diverse fields of practice. The objective was to analyze this track in the training of education professionals at a public university in northeastern Mexico, with the purpose of using the information to compare it—locally and nationally—with other educational programs. A qualitative methodology was followed under the interpretive phenomenological paradigm in order to situate experiences and understand the phenomenon. An interview guide was applied to three focus groups with 110 participants distributed across three cohorts of the program, in two sessions lasting two and a half hours each (5 hours in total), with selection criteria including completion of 50% of the curriculum, faculty recommendation, and academic experience. Three main categories were identified: the curricular structure of the psychopedagogical track; recommendations to the curriculum to expand this track; and the labor field and practical experiences. In addition, a documentary analysis was conducted of two other local programs (UMM and UDEM) and three national programs (UNAM, UABC, and UNISON) to identify courses based on students’ opinions. These findings suggest alternatives for improving and ensuring the fulfillment of the psychopedagogical curricular track within the professional profile of education professionals.